Training refugees: Lights and shadows in the context of the self-reliance strategy implemented in Uganda - Mastrorillo, Marina; Scognamillo, Antonio; Ignaciuk, Adriana (Informa UK Limited, 2024)
Uganda currently hosts about 1.5 million refugees. Only a fraction is likely to revert to their home countries. Therefore, a key policy question is how to help the displaced communities to integrate into Uganda’s economic system. One strategy to integrate the refugees in the local economy is to provide them trainings on agricultural production or off-farm business opportunities. This study, using panel data coming from the Resilience Index Measurement and Analysis (RIMA) survey, estimates the causal impact of training activities on refugees’ food security and market access. Potential endogeneity issues are addressed through an instrumental variable approach. Results indicate that, on average, agricultural training increases both market access and food security. However, disentangling the effect across population sub-groups, findings highlight substantial differences. The impact of business training, instead, is never statistically different from zero, except for the households experiencing economic losses due to COVID-19, who mainly benefit in terms of food security. These results highlight the existence of challenges to integrate the refugees in the national economy and indicate that training activities are necessary but not sufficient to reach self-reliance.